First cave records for Palearctic burrower bugs (Hemiptera: Heteroptera: Cydnidae) from Tajikistan, with a checklist of the World Cydnidae associated with caves - Kłys, Grzegorz; Lis, Jerzy A. (Zootaxa, 2013)
Species of the family Cydnidae (known as the “burrower bugs”) live usually on or in the ground; sometimes they even burrow deep into the soil (e.g., Froeschner 1960; Schaefer 2003; Linnavuori 1993; Lis 1994, Lis et al. 2000). However, data on burrower bugs associated with caves and their environment are very rare; only ten species of three Cydnidae subfamilies were hitherto recorded from this type of habitat (see the checklist at the end of this paper).